The role of verbal and visuo-spatial working memory in the encoding of virtual routes by children and adults. Issue 7 (3rd October 2018) - Nys, Marion; Hickmann, Maya; Gyselinck, Valérie
ABSTRACT: This study aims to understand the role of verbal and visual-spatial components of working memory in children's encoding of virtual routes. Children aged 8 and 10 years and adults memorised virtual routes in three conditions involving either a secondary task (visuo-spatial or verbal) or no such task (control). The learning phase was followed by four tasks evaluating their spatial representation: producing a description of the route, verbally and visually recognising landmarks, and choosing directions. Results first supported an increase with age in the quantity and quality of landmarks and directions mentioned and recognised in both verbal and visuo-spatial tasks. Second, both concurrent tasks were detrimental to spatial memory although this was more striking for the visuo-spatial task. Moreover, interference effects depended on age and on the format used for retrieval. Overall, our results provide a novel contribution to our understanding of the development of spatial models.